2022
DOI: 10.1038/s41420-022-01086-2
|View full text |Cite
|
Sign up to set email alerts
|

Ubiquitin-specific protease 7 regulates myocardial ischemia/reperfusion injury by stabilizing Keap1

Abstract: Myocardial ischemia/reperfusion (I/R) injury is a complex pathological process that is still not fully understood. The oxidative stress response has a critical role in the occurrence and progression of myocardial ischemia/reperfusion injury. This study investigated the specific mechanism of ubiquitin-specific protease 7 (USP7) regulation of myocardial ischemia/reperfusion injury from the perspective of proteasome degradation and its relation with the Keap1 pathway, a vital regulator of cytoprotective responses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…In addition to the degradation of NRF2 being mediated by the Keap1-Cul3-Rbx1 complex, Keap1 itself is negatively regulated via ubiquitination and degradation by the proteasome [ [20] , [21] , [22] ]. Given that MK-886 reduced Keap1 protein levels but not mRNA levels in the hearts of I/R mice ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to the degradation of NRF2 being mediated by the Keap1-Cul3-Rbx1 complex, Keap1 itself is negatively regulated via ubiquitination and degradation by the proteasome [ [20] , [21] , [22] ]. Given that MK-886 reduced Keap1 protein levels but not mRNA levels in the hearts of I/R mice ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to NRF2 ubiquitination and degradation, an alternative mechanism regulating NRF2 protein stability has been discovered. Several ubiquitin-related enzymes, including E3 ligases (TRIM15 and TRIM25) and deubiquitinase (USP7), can regulate keap1 ubiquitin-mediated proteasomal degradation in cancer cells and cardiac tissues [ [20] , [21] , [22] ]. In current study, we also detected the expression levels of TRIM15, TRIM25 and USP7 in the heart at 6–72 h following I/R and found that the mRNA levels of these enzymes were not statistically different among the various time points ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…USP7, as an important deubiquitinase, has been reported to participate in different biological activities by stabilizing and deubiquitylating several substrate proteins, such as MDM2, SMAD3, PTEN, NF-κB, Keap1, NLRP3 and others ( Colleran et al, 2013 ; Huang et al, 2021 ; Xu et al, 2022 ). A study has shown that the USP7 inhibitor p22077 blocks inflammation response and the activation of NLRP3 inflammasome ( Palazon-Riquelme et al, 2018 ), while activation of NLRP3 inflammasome involved in cardiac remodeling, suggesting that USP7 may play an important role in cardiac remodeling.…”
Section: Discussionmentioning
confidence: 99%
“…Increasing evidence has demonstrated that DUBs have a crucial role in cardiovascular diseases, such as cardiac hypertrophy, myocardial infarction, atrial fibrillation, heart failure, and others ( Liu et al, 2016 ; Bi et al, 2020a ; Bi et al, 2020b ; Hu et al, 2021 ). USP7 (also called Herpesvirus-associated ubiquitin-specific protease, HAUSP), the first identified DUBs, participated in cell proliferation, DNA damage response, tumourigenesis, inflammation, and apoptosis by regulating its substrates, such as MDM2/p53, PTEN, FOXO4, NF-κB, and other target proteins ( Khoronenkova et al, 2012 ; Smits and Freire, 2016 ; Xu et al, 2022 ). Recently, two studies found that the expression of USP7 was significantly increased under hypoxia in cardiomyocytes, while its inhibition or knockdown of USP7 can protect the heart from hypoxia-induced cardiomyocyte injury or myocardial ischemia/reperfusion injury ( Xue et al, 2021 ; Xu et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation